Application of conjugated materials in muscle movement recovery process - Zhang, Dengfeng; Fan, Guanxi (Frontiers in Chemistry, 2023)
Conjugate materials have a good application effect in muscle movement recovery. This article aims to provide more references for the practical application of conjugated materials in sports recovery. This paper takes the students of the local physical education college as the experimental object, and selects the students who have sports muscle fatigue or injury for the test. In this paper, they are randomly divided into two groups: the experimental group and the control group, with 19 students in each group. The experimental group used the conjugate material in this paper for muscle movement recovery, while the control group used the traditional method for muscle movement recovery. This paper tested the peak torque, total work done, maximum radial displacement, and contraction time of two groups of students after initial exercise and muscle recovery. The experimental results showed that after 80 h of muscle movement recovery, the peak torque values of isometric contraction (264.59) and concentric contraction (160.81) of students in the experimental group were higher than those of students in the control group (233.79) and concentric contraction (130.43), and the difference was statistically significant (p < 0.05); the isometric contraction time (30.02) and concentric contraction time (29.31) of the experimental group were also higher than those of the control group (27.31) and concentric contraction time (24.58), which was statistically significant (p < 0.05). This study shows that conjugated materials have a significant effect on promoting muscle recovery. They not only help to increase the peak torque of muscle isometric contraction and concentric contraction, but also increase the time of muscle contraction and improve muscle mass.